(3eNJUQ TQM GdebfY aj Yde CHj ebQY aj GdejbGJs - (3GdeQZJj, eMeO Hf SYjO Hf eMeO, J(B1089(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj ef YdjfGYde ChbGJ Gddjd hGdfgGQCRgGQ QhVI GdGYJHGQ hRjf GdSeGA HeUGHjMs
(3BNQgG (B:s
(3hPdc Cf JbSje JSY eGFI Ydi ebGe GdKdKhbO PcQ HYV GdCFeI Cf gPG gh (B() (3eG jRjO hgh YTQ KdK GdSGYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 139s
(3eYLe GdeDdajf(B: 3 / 324s
(3EjVGM Gdecfhf(B: 2 / 548s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3gjFIs